Outcome of 313 Czech Patients With IgA Nephropathy After Renal Transplantation - Maixnerova, Dita; Hruba, Petra; Neprasova, Michaela; Bednarova, Kamila; Slatinska, Janka; Suchanek, Miloslav; Kollar, Marek; Novak, Jan; Tesar, Vladimir; Viklicky, Ondrej (Frontiers in Immunology, 2021)
The recurrence of IgA nephropathy (IgAN) after kidney transplantation occurs in 20–35% of patients. The main aim of this study is to evaluate risk factors affecting the course of IgAN after renal biopsy of native kidney and kidney transplant. We evaluated clinical parameters and histological findings at the time of biopsy of native kidney and after kidney transplantation in 313 patients with IgAN with a follow-up of up to 36 years. Using hierarchical clustering method, patients with graft failure (n=50) were divided into two groups based on the mean time from kidney transplant to graft failure (11.2 versus 6.1 years). The time-to-graft failure corresponded well to the time from the renal biopsy of native kidney to end-stage renal disease (5.9 versus 0.4 years). Body mass index, proteinuria, microscopic hematuria, histological evaluation of fibrosis, and crescents at the time of renal biopsy of native kidney were the main variables for the differentiation of the two groups. Higher age of kidney-transplant donor, histological recurrence of IgAN, antibody-mediated rejection, and the onset of microscopic hematuria and proteinuria within 1 year after kidney transplant were also associated with worse graft survival in multivariate Cox regression analysis.